Солнечный коллектор для бытового устройства - Михайлов, С. А. (ХНУРЕ, 2012)
A flat photo-electric collector contains the great number of the separate photo-electric elements. Collector closed from above by a glass or plastic transparent panel. Sun energy will be transformed by these elements in electric power with small permanent tension
Keywords: солнечный коллектор